Waste pig blood-derived 2D Fe single-atom porous carbon as an efficient electrocatalyst for zinc-air batteries and AEMFCs - Kim, Hee Soo; Lee, Jiho; Jang, Jue-Hyuk; Jin, Haneul; Paidi, Vinod K.; Lee, Soo-Hyoung; Lee, Kug-Seung; Kim, Pil; Yoo, Sung Jong (ELSEVIER, 2021)
Biomass is a useful precursor for manufacturing electrocatalysts because it is highly abundant, eco-friendly, and is composed of organic materials that include Fe and nitrogen precursors. Among the numerous waste biomass types, slaughtered pig blood contains a high concentration of Fe-porphyrin inside the hemoglobin, and this characteristic makes it an ideal precursor for fabricating a bio-inspired Fe-N-C oxygen reduction reaction (ORR) catalyst. Here, Zinc (Zn)-hydrolysates are obtained from purified waste pig blood was used as a porous carbon source for two-dimensional (2D) sheet-like porous single-atom electrocatalysts. In addition, pig blood provides Fe single-atom catalytic sites derived from hemoglobin in (Zn)-hydrolysates and shows excellent ORR activity by retaining excellent mass transfer due to the presence of mesopores generated by Zn activation under NH3 pyrolysis Furthermore, one of the catalytic materials is a Zn-incorporated Fe single-atom porous carbon catalyst (designated Zn/FeSA-PC)/950/NH3, was successfully integrated as an Anion Exchange Membrane Fuel Cells (AEMFCs) and Zn-Air Batteries (ZABs) where it supported maximum power densities of 352 and 220 mW/cm2, respectively. This study demonstrates the new designs and preparation procedures for high-performance electrocatalysts that can be manufactured at low cost from abundant and renewable blood biomass.
Keywords: OXYGEN REDUCTION REACTION; N-C; LOW-COST; BIOMASS; PERFORMANCE; CATALYSTS; SPHERES; AGGREGATION; SITES